EFFECT OF HIGH SALT STRESS ON PHOTOSYNTHETIC ELECTRON TRANSPORT ACTIVITIES IN THE CYANOBACTERIUM, SPIRULINA PLATENSIS - P. SREEVANI,; G. BHANUMATHI,; S. ARIF MOHAMMAD,; S. D. S. MURTHY, (The Bioscan, 2011)
In this present study an attempt has been made to study the effect of high salt stress (0.8M NaCl) on the electron transport properties of the intact cells of Spirulina platensis. 9 h treatment of salt stress (0.65 M-0.8 M NaCl) caused significant inhibition in both whole chain electron transport and Photosystem (PS II) catalyzed electron transport assay. A 42% inhibition was noticed at 0.8M NaCl treatment. Similarly the loss in variable Chl a fluorescence was also observed. The light intensity measurements of PS II activity clearly demonstrated that the inhibition was more at light saturating conditions (400 Wm-2) than that at light limiting conditions (50 Wm-2). The possible reason for the loss of PS II activity could be alterations in light harvesting complex of the above cyanobacteria.